EFEKTIVITAS MEDIA PUZZLE UNTUK MENINGKATKAN KEMAMPUAN MENYUSUN KALIMAT BAGI CEREBRAL PALSY - Alan Tresno Setiawan (Jurnal Penelitian Pendidikan Khusus, 2012)
The observation that researchers do in the SLB Al Islaah Padang. Investigators found a child with Cerebral Palsy who experience problems with the preparation of a sentence, especially in the form subjek, prediket, objek and keterangan (SPOK). Though her condition was good at reading. Based on this study aims to improve the ability to construct a sentence SPOK children through the media Puzzle. This study uses a quantitative approach to experimentation in the form of Single Subject Research (SSR) with a research design using design A - B – A. Target behavior is the percentage of children's ability to construct a sentence SPOK by answering questions correctly as many as ten questions on the worksheet the students in the same relative time is 25 minutes. Data taken through the procedure of marking the checklist questions on a number of questions answered correctly on the student work sheet. Data analysis techniques are used based on the observed data in the form of Visual Analysis of Graphs. The results are analyzed include the number of observations at five times the baseline condition and treatment conditions as much as eight times. The results of this study indicate that the ability to construct a sentence Puzzle media SPOK for children increased. This is evident from the results of the analysis is the tendency to increase. In the baseline condition (A1) the child is not able to completely answer the question correctly, but after being given treatment in the treatment condition (B) the child is able to answer eight questions correctly out of ten questions are given and the percentage of children's ability to rise to 80% obtained by the calculation formula. and at baseline (A2) the child's attainment of 60% on last observation, it is strong enough to be evidence that an effective media puzzle. Researchers suggest that teachers and researchers in order to use the media later in the teaching Puzzle SPOK make sentences for learners.